Environmental management for dredging sediments - The requirement of developing nations - Manap,N; Voulvoulis,N (Journal of Environmental Management, 2015)
Scientific research has characterized the effects of dredging, an underwater excavation process for navigational purposes or material extraction, and has shown its association with a number of chemical, physical and biological impacts. Due to this, much environmental management has been applied in the dredging industry in order to manage its detrimental effects. However, developing nations may have different approaches towards their dredging environmental management to compare to their companions with higher economic strength. Moreover, scientific evidence to make an informed decision is often lacking, hence affecting the number of research executed at these nations, limiting their efforts to preserve the environment. This paper reviews the dredging environmental impacts and its two important factors, dredging technology and sediment characteristic, that determine the magnitude of impacts through literature review, and discusses the need for a more integrated dredging environmental management to be developed for developing nations.